2019
DOI: 10.1111/jce.14206
|View full text |Cite
|
Sign up to set email alerts
|

A nurse‐led implantable loop recorder service is safe and cost effective

Abstract: Introduction Implantable loop recorders (ILR) are predominantly implanted by cardiologists in the catheter laboratory. We developed a nurse‐delivered service for the implantation of LINQ (Medtronic; Minnesota) ILRs in the outpatient setting. This study compared the safety and cost‐effectiveness of the introduction of this nurse‐delivered ILR service with contemporaneous physician‐led procedures. Methods Consecutive patients undergoing an ILR at our institution between 1st July 2016 and 4th June 2018 were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The extended sensing vector of ≈70 mm versus <50 mm in other contemporary ICM models yields a larger mean R-wave amplitude in BIOMONITOR III (0.73 mV) than in other ICM modes (≤0.60 mV), which may improve sensing capabilities. 7,[14][15][16] Furthermore, R-wave amplitudes were significantly larger (mean 0.80 vs. 0.62 mV) when the device was inserted along the heart axis J o u r n a l P r e -p r o o f (54.2% of pts) than when it was inserted parasternally (41.3% of pts). Therefore, the insertion parallel to the heart's long axis can be recommended as a first-line solution in clinical practice.…”
Section: Sensing Qualitymentioning
confidence: 94%
“…The extended sensing vector of ≈70 mm versus <50 mm in other contemporary ICM models yields a larger mean R-wave amplitude in BIOMONITOR III (0.73 mV) than in other ICM modes (≤0.60 mV), which may improve sensing capabilities. 7,[14][15][16] Furthermore, R-wave amplitudes were significantly larger (mean 0.80 vs. 0.62 mV) when the device was inserted along the heart axis J o u r n a l P r e -p r o o f (54.2% of pts) than when it was inserted parasternally (41.3% of pts). Therefore, the insertion parallel to the heart's long axis can be recommended as a first-line solution in clinical practice.…”
Section: Sensing Qualitymentioning
confidence: 94%
“… 3 , 32 Additionally, it creates a stream of additional revenue and profit for hospitals. 33 , 34 An umbrella review, after summarizing a large body of evidence, cautiously provided unbiased results indicating that NLCs offer comparable or superior care to usual care with high levels of patient satisfaction. This is because NLCs reduce patients’ waiting times while maintaining their safety and save healthcare resources and costs.…”
Section: Discussionmentioning
confidence: 99%
“…46,49,56 In an observational study including 540 patients, implant site infection was observed in 1.5%, pain requiring device removal or revision in 1.5%, hypertrophic scar in 0.2% and device malfunction in 0.2%. In addition, Lim et al 57 demonstrated that the Reveal LINQ TM (Medtronic©, Minnesota, USA) could be safely implanted in the outpatient setting by nurses, leading to significant cost reductions compared with physician implants in the electrophysiology laboratory.…”
Section: Implantable Cardiac Monitorsmentioning
confidence: 99%